2021
DOI: 10.1007/s12035-020-02245-1
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection in the Central and Peripheral Nervous System-Associated Morbidities and Their Potential Mechanism

Abstract: The recent outbreak of SARS-CoV-2 infections that causes coronavirus-induced disease of 2019 (COVID-19) is the defining and unprecedented global health crisis of our time in both the scale and magnitude. Although the respiratory tract is the primary target of SARS-CoV-2, accumulating evidence suggests that the virus may also invade both the central nervous system (CNS) and the peripheral nervous system (PNS) leading to numerous neurological issues including some serious complications such as seizures, encephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 181 publications
3
64
0
7
Order By: Relevance
“…Autopsy, animal, and organoid model studies show that, like SARS-CoV, SARS-CoV-2 is able to reach and infect cells of the CNS, infect neurons, and produce neuroinflammation ( Matschke et al, 2020 ; Song et al, 2020 ; Song et al, 2021 ). Indeed, SARS-CoV-2 may be capable of transport up and down nerves and neuronal axons ( Lima et al, 2020 ; Rangon et al, 2020 ; Song et al, 2020 ; Karuppan et al, 2021 ).…”
Section: The Neuroinvasive and Neurotrophic Potential Of Sars-cov-2mentioning
confidence: 99%
“…Autopsy, animal, and organoid model studies show that, like SARS-CoV, SARS-CoV-2 is able to reach and infect cells of the CNS, infect neurons, and produce neuroinflammation ( Matschke et al, 2020 ; Song et al, 2020 ; Song et al, 2021 ). Indeed, SARS-CoV-2 may be capable of transport up and down nerves and neuronal axons ( Lima et al, 2020 ; Rangon et al, 2020 ; Song et al, 2020 ; Karuppan et al, 2021 ).…”
Section: The Neuroinvasive and Neurotrophic Potential Of Sars-cov-2mentioning
confidence: 99%
“…Until then, models of SARS-CoV2 damage of ECs should consider direct infection via ACE2 as a hypothesis to be confirmed. Finally, ACE2 is not the only possible endothelial receptor for viral entry: other molecules including neuropilin-1, as well as integrings, have been suggested as possible receptors for the virus as well [ 155 158 ], but their role in supporting SARS-CoV-2 infection of ECs remains to be demonstrated.…”
Section: Microthrombosis and Mechanisms Of Vascular Damage In Covid-19mentioning
confidence: 99%
“…In a few cases of Miller-Fisher syndrome concomitant with COVID-19, commonly reported manifestations included perioral paresthesia, ataxia, impaired vision, ophthalmoplegia, and generalized areflexia [ 74 ]. Fortunately, two-thirds of patients showed improvement after administration of immunoglobulin [ 75 ].…”
Section: Pns Manifestationsmentioning
confidence: 99%
“…There is a growing concern regarding the long-term sequelae of COVID-19, particularly involving the nervous system, as cases of patients recovering from initial symptoms while beginning to present new neurological manifestations are now emerging. It was demonstrated that some patients had double vision, hallucinations, disorientation, and impaired attention, quadriplegia, facial paralysis, and hypogeusia even 6 months after infection [ 75 ]. A prospective cohort study in France assessed the clinical status of COVID-19 patients 4 months after discharge.…”
Section: Long Covid? a Glimpse Into The Neuronal Systemmentioning
confidence: 99%